(untitled) (Texas Journal of Engineering and Technology, 2024)
In this article, the main purpose of agricultural land monitoring with the help of Geoinformation technologies, Geographic Information Systems (GIS), areas of application of GIS in agriculture in Uzbekistan were studied.